2013
DOI: 10.1051/0004-6361/201118001
|View full text |Cite
|
Sign up to set email alerts
|

HαMoreton waves observed on December 06, 2006

Abstract: Context. We present high temporal resolution observations of a Moreton wave event detected with the Hα Solar Telescope for Argentina (HASTA) in the Hα line 656.3 nm, on December 6, 2006. Aims. The aim is to contribute to the discussion about the nature and triggering mechanisms of Moreton wave events. Methods. We describe the HASTA telescope capabilities and the observational techniques. We carried out a detailed analysis to determine the flare onset, the radiant point location, the kinematics of the disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 27 publications
(62 reference statements)
3
22
2
Order By: Relevance
“…In Hα, regions exhibiting double traces are noticeable (see features indicated by light-blue arrows in sectors 36 -39 of Figure 2a), suggesting the presence of more than a single coronal perturbation or a complex physical process that originates the differing chromospheric emissions. Other authors have suggested the presence of more than one Moreton-wavefront in the vicinity of an AR Francile et al, 2013). However, in our case the spatial separation between these two fronts is not large enough to conclude about their presence on a firm basis.…”
Section: About the Correspondence Between The Analyzed Regimescontrasting
confidence: 93%
See 3 more Smart Citations
“…In Hα, regions exhibiting double traces are noticeable (see features indicated by light-blue arrows in sectors 36 -39 of Figure 2a), suggesting the presence of more than a single coronal perturbation or a complex physical process that originates the differing chromospheric emissions. Other authors have suggested the presence of more than one Moreton-wavefront in the vicinity of an AR Francile et al, 2013). However, in our case the spatial separation between these two fronts is not large enough to conclude about their presence on a firm basis.…”
Section: About the Correspondence Between The Analyzed Regimescontrasting
confidence: 93%
“…We estimate the kinematic characteristics of the Moreton wavefronts by fitting power-law curves (Warmuth et al, 2004a;Francile et al, 2013) for every sector of interest to the average spline obtained, as indicated above. These curves are suitable to fit smoothly kinematic trajectories with non-constant accelerations.…”
Section: Surface Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Warmuth et al, 2004a;Narukage et al, 2008;Muhr et al, 2010;Balasubramaniam et al, 2010;Warmuth, 2010;Asai et al, 2012;Francile et al, 2013). The initial velocities are in the range of 600 -1200 km s -1 and decline to ≈ 500 km s -1 before the Hα wave signatures vanish.…”
Section: Deceleration Of a Single Disturbancementioning
confidence: 98%